Hak Tersangka atas Peradilan yang Adil dan Tidak Memihak dalam Kerangka Due Process of Law - Beben Muhammad Bachtiar; Sarip Hidayat (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2025)
The suspect's right to a fair and impartial trial within the framework of Due Process of Law in the criminal justice system in Indonesia. The method used here is the normative legal research method through a statutory approach. The results of the study indicate that the existence of Due Process of Law in the criminal justice system can create an integrated criminal justice system, which means that the role of Due Process of Law is very important. In addition, the criminal justice system in Indonesia has been proven to have sufficiently fulfilled human rights protection, this can be seen in the regulations contained in the Criminal Procedure Law, namely in the recognition of equality before the law, the application of the presumption of innocence principle, the fulfillment of various suspect rights, and the inclusion of several principles in criminal procedure law.